To generate greater economic benefit from visiting ships : to develop Singapore into a liquefied natural gas HUB - Shi, Mengqi (2017)
Situated right at the crossroad of major trade routes between the East and the West, Singapore is well-known as a global maritime hub with world’s busiest shipping traffic. The maritime cluster has always been vital to Singapore’s economy. It is then crucial to study how to further generate greater economic benefits from visiting ships. This part of the research focuses on the aspect of developing Singapore into a liquefied natural gas (LNG) hub. It was conducted using both primary and secondary research. A wide range of literature and statistics were collected and analysed to gain an in-depth understanding of the global and regional LNG market, as well as the recent developments in LNG shipping and supply chain. The primary research involved conducting interviews with relevant industry experts from various backgrounds to obtain first-hand information and further substantiate the analysis. The feasibility was first examined. Given the rapid growth of LNG trades and the existence of potential business opportunities such as regional break bulk and re-export services, firmly supported by Singapore’s existing maritime cluster and infrastructure, it can be inferred that the development of a regional LNG hub is a viable strategy. Following that, the possible resulting economic benefits were identified. At last, five key areas of development were recommended accordingly, including establishing inter-governmental partnerships, promoting spot LNG trades, expanding terminal infrastructures, developing a diversified LNG ecosystem, and introducing conducive policies, as well as the legal and technical framework. In overall, this study revealed a rather optimistic future. With necessary actions taken, Singapore can gear up to be a regional LNG hub, which potentially attracts substantial shipping traffic and generates great economic benefits across industries.